Risk assessment of balance and falls in elderly patients due to stroke - Pietro Araújo dos Santos (Kairós Gerontologia, 2012)
The aim of this study was to evaluate the balance and risk of falls in elderly patients with Stroke treated at the Municipal Center for Prevention and Rehabilitation Physics of the Municipality of Jequié (NUPREJ), (Bahia). Instruments were used as the Mini Mental State Examination, a social demographic questionnaire and the Berg Balance Scale. The results showed a decrease in balance, indicating that this was a risk factor for falls.